Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3349/ymj.2022.63.7.619
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin Ameliorates Nonalcoholic Fatty Liver Disease by Regulating Lipid Metabolism and Inhibiting Inflammation through Induction of Autophagy

Abstract: Purpose Nonalcoholic fatty liver disease (NAFLD) is closely associated with metabolic diseases, including obesity and diabetes, and has gradually become the most common cause of chronic liver disease. We investigated the effects of sodium glucose cotransporter 2 (SGLT2) inhibitor canagliflozin on NAFLD in high-fat diet (HFD)-induced obese mice and possible underlying mechanisms. Materials and Methods Male C57BL/6 mice were fed a normal-diet, HFD, or HFD with canaglifloz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…First, SGLT2 inhibitors consistently enhance autophagic flux (including mitophagy) in the heart and kidney; the action to augment autophagy is seen in tissue harvested from chronically treated animals as well as in isolated cell cultures perfused with SGLT2 inhibitors (Table 1). [155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172][173] Second, SGLT2 inhibitors mute the generation of reactive oxygen species, enhance antioxidant mechanisms, and mitigate endoplasmic reticulum stress. 165,167,169,[174][175][176] Third, SGLT2 inhibitors accelerate the disposal of injured mitochondria, restore healthy mitochondrial function, and promote mitochondrial biogenesis 167,169 ; the increase in mitochondrial mass is a characteristic feature of the action of these drugs on electron microscopy.…”
Section: Action Of Nutrient Sensors To Influence Cellular Stress By M...mentioning
confidence: 99%
“…First, SGLT2 inhibitors consistently enhance autophagic flux (including mitophagy) in the heart and kidney; the action to augment autophagy is seen in tissue harvested from chronically treated animals as well as in isolated cell cultures perfused with SGLT2 inhibitors (Table 1). [155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172][173] Second, SGLT2 inhibitors mute the generation of reactive oxygen species, enhance antioxidant mechanisms, and mitigate endoplasmic reticulum stress. 165,167,169,[174][175][176] Third, SGLT2 inhibitors accelerate the disposal of injured mitochondria, restore healthy mitochondrial function, and promote mitochondrial biogenesis 167,169 ; the increase in mitochondrial mass is a characteristic feature of the action of these drugs on electron microscopy.…”
Section: Action Of Nutrient Sensors To Influence Cellular Stress By M...mentioning
confidence: 99%
“…Some of the well-described drugs that also show pro-autophagic activity in this class are metformin [ 87 ], rapamycin [ 88 ], statins [ 89 ], pioglitazone [ 90 ], fibrates [ 91 ], canagliflozin [ 92 ], verapamil [ 93 ], and carbamazepine [ 94 ].…”
Section: Pharmacological and Nonpharmacological Inducers Of Autophagy...mentioning
confidence: 99%
“…Given that NASH can be accompanied by fibrosis, the main risk factor for mortality due to hepatic causes of NAFLD [ 7 ], in recent years, there has been significant research into therapies aimed at controlling NASH. However, no Food and Drug Administration (FDA)-approved NAFLD-specific medications are currently available [ 8 ]. For this reason, it is very important to insist on the study of the pathogenic mechanisms involved in the progression of NAFLD/NASH to demonstrate possible therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Given the suggested beneficial role that autophagy seems to have in NAFLD pathogenesis and given that there is not yet a specific drug approved by regulatory agencies to treat this hepatic disorder, drugs involving the autophagy system have begun to be investigated for the treatment of NAFLD [ 8 , 20 , 21 , 22 ]. In a recent study in animal models, it was suggested that the endocannabinoid system, which is known to be implicated in the pathogenesis of NAFLD, might mediate its role through autophagy mechanisms [ 23 ].…”
Section: Introductionmentioning
confidence: 99%